ANALYSIS OF IMPLEMENTATION OF FINANCIAL ACCOUNTING STANDARDS OF MSMEs TO DRIVE MSMEs IN BOGOR CITY TO RISE DURING POST-COVID-19 PANDEMIC - Iis Wahyuni (Kesatuan Press, 2022)
It was recorded that there were 65,000 MSMEs in the city of Bogor which were registered in the MSME Service Office data, which experienced a significant decline in sales during the COVID-19 pandemic. The role of accounting for MSMEs is to assist in financial control, operations, reporting, and planning. This study aims to determine the business conditions of MSME actors during the COVID-19 pandemic. The results of the study revealed that the business conditions of MSME actors in the city of Bogor during the Covid-19 pandemic experienced a decline in sales turnover, some even had to terminate their employment. The role of MSME financial accounting standards during the COVID-19 pandemic has not helped much, only to facilitate administration in obtaining government stimulus assistance and tax incentives, to assist in obtaining government capital loans and other financial institutions, and assisting in making business decisions during the pandemic and post-pandemic. pandemic.